MODEL OF MANAGEMENT FOR IMPLEMENTING A MULTIPLE INTELLIGENCES BASED TALENT PROGRAM IN OPTIMIZING STUDENTS POTENTIAL - Nasyilla Putri Nirwan; Ummah Karimah; Mochamad Daffa Akmal (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Contemporary education emphasizes the comprehensive development of students’ potential, extending beyond academic achievement to include diverse talents, interests, and intellectual capacities. This paradigm aligns with Howard Gardner’s theory of Multiple Intelligences, which asserts that each individual possesses a unique configuration of intelligences that must be systematically identified and nurtured. Within the framework of Islamic education, such holistic development reflects the concept of insān kāmil, a well-balanced individual who grows harmoniously in intellectual, emotional, spiritual, and social dimensions. Therefore, schools are required to design structured programs that move beyond cognitively oriented instruction and provide opportunities for students to explore and actualize their multiple intelligences.This study aims to analyze the implementation of a talent development program in supporting students’ Multiple Intelligences at SMP Muhammadiyah 8 Jakarta, focusing on planning, implementation, and evaluation from a school management perspective. A qualitative approach with a case study design was employed. Data were collected through in-depth interviews, observation, and document analysis involving school leaders, teachers, students, and parents.The findings indicate that the program is designed through initial potential assessments, flexible curriculum planning, and collaboration with professional trainers. Implementation emphasizes personalized and sustainable development of multiple intelligences, while evaluation is conducted comprehensively, covering cognitive, affective, and psychomotor aspects. The study concludes that the Multiple Intelligences-based talent program effectively optimizes students’ holistic development and supports the school’s vision of nurturing academically competent and morally grounded generations.